First report of the cactus cyst nematode, Cactodera cacti, from a cactus garden in Idaho - Skantar, Andrea M (Journal of nematology, 2019)
In April 2018, a cyst nematode was discovered from soil samples collected from a cactus garden collection in Meridian, Ada County, Idaho, USA. The cactus garden collection field reported was observed with localized areas of heavily stunted plants. Roots from affected plants displayed moderate numbers of nematode cysts. Living nematode juveniles (J2) recovered from the cysts were examined morphologically and molecularly for species identification which indicated that the specimens were Cactodera cacti. This is the first report of the cactus cyst nematode, C. cacti in Idaho